Evaluating the Impact of a School-Based Youth-Led Health Education Program for Adolescent Females in Mumbai, India. Issue 1 (26th August 2020) - Shankar, Priya; Sievers, Dana; Sharma, Ricky
Background: India's 120 million adolescent girls often have limited opportunities to receive health education, as health-related content in school curricula can be minimal, and the few existing external interventions for this demographic rarely cover multiple topics. Objectives: This study conducted a program evaluation of Girls Health Champions, a school-based peer education intervention in Mumbai, India that educates girls about leading causes of adolescent morbidity and mortality, including nutrition, mental health, and sexual & reproductive health. Methods: Female participants ages 12 to 16 in the eighth, ninth, and tenth standards were recruited at five participating schools in Mumbai, India to learn a multi-topic health curriculum from their peers, with a subset of ninth standard participants in each school trained as the peer educators. Using a quasi-experimental design, participant survey data was collected three times during the 2016–2017 academic year: at baseline, immediately following the peer-led education sessions, and five months following these sessions. Outcomes of interest included change in knowledge levels and health attitudes following the intervention, as well as retention at mid-year. An additional outcome was the change in self-reported leadership skills of peer educators before and after participating. Findings: Compared to baseline, participants demonstrated statistically significant increases in knowledge levels (+48%, p < 0.001) and positive shifts in health-related attitudes (+42%, p < 0.001). These changes were maintained at mid-year (+29% for knowledge levels, p < 0.001; +37% for attitudes, p < 0.001). Findings were consistent when data was stratified by standard and peer educator status (peer educators versus non-peer educators). Peer educators also demonstrated a statistically significant increase in their interest in health promotion. Conclusions: This study demonstrates the effectiveness of the peer education delivery model and finds school-based, peer-led programs covering a range of adolescent health topics can significantly increase knowledge and shift attitudes of program participants. Such benefits can accrue to both peer educators and non-peer educator program participants.